The role of doulas in supporting perinatal mental health – a qualitative study - Quiray, Joanne; Richards, Elizabeth; Navarro-Aguirre, Yesenia; Glazer, Debra; Adachi, Jamie; Trujillo, Emily; Perera, Dila; Garcia, Elizabeth Perez; Bhat, Amritha (Frontiers in Psychiatry, 2024)
Objective: The perinatal period presents several opportunities to identify and treat perinatal mental health and substance use disorders by integrating into existing care pathways. We aimed to examine the role of birth doulas in supporting their clients' perinatal mental health.Methods: Thematic content analysis of focus groups with doulas, and interviews with doula clients was used to characterize the doula-client relationship, investigate whether and how doulas provide mental health and substance use support, and identify barriers and recommendations for doulas to support their clients' mental health. Participants were doula clients from communities underserved due to race, income, language and culture.Results: Doulas and clients reported positive relationships, supported by congruence in culture, language, and lived experiences. Doulas varied in their confidence in identifying perinatal mental health problems, though most agreed that doulas could support their clients' mental health to different degrees. Barriers to engaging in perinatal mental health treatments included low perceived need and socio-economic burden.Conclusions: With adequate support and training, doulas can play an important role in supporting their client's emotional well-being.